A proposed interplay between peroxidase, amine oxidase and lipoxygenase in the wounding-induced oxidative burst in Pisum sativum seedlings. (April 2015) - Roach, Thomas; Colville, Louise; Beckett, Richard P.; Minibayeva, Farida V.; Havaux, Michel; Kranner, Ilse
Graphical abstract: Wounding-induced production of superoxide by peroxidases in pea seedlings requires hydrogen peroxide from amine oxidases and can be enhanced by linoleic acid. Highlights: Wounding pea seedlings led to rapid release of fatty acids, H2 O2 and O2 − . Amine oxidases produced H2 O2 needed for O2 − production. Exogenous linoleic acid enhanced O2 − production, but was also dependent on H2 O2 . Peroxidases (Prx) were more active in producing O2 − than NADPH oxidases. A Prx released from wounded seedlings produced O2 − in the presence linoleic acid. Abstract: Plant surfaces form the barrier between a plant and its environment. Upon damage, the wound healing process begins immediately and is accompanied by a rapid production of extracellular reactive oxygen species (ROS), essential in deterring pathogens, signalling responses and cell wall restructuring. Although many enzymes produce extracellular ROS, it is unclear if ROS-producing enzymes act synergistically. We characterised the oxidative burst of superoxide (O2 − ) and hydrogen peroxide (H2 O2 ) that follows wounding in pea ( Pisum sativum L.) seedlings. Rates of ROS production were manipulated by exogenous application of enzyme substrates and inhibitors. The results indicate significant roles for di-amine oxidases (DAO) and peroxidases (Prx) rather than NADPH oxidase. The burst of O2 − was strongly dependent on the presence of H2 O2 produced by DAO. Potential substrates released from wounded seedlings included linoleic acid that, upon exogenous application, strongly stimulated catalase-sensitive O2 − production. Moreover, a 65 kD plasma membrane (PM) guaiacol Prx was found in the secretome of wounded seedlings and showed dependence on linoleic acid for O2 − production. Lipoxygenases are suggested to modulate O2 − production by consuming polyunsaturated fatty acids in the apoplast. Overall, a O2 − -producing mechanism involving H2 O2 -derived from DAO, linoleic acid and a PM-associated Prx is proposed.